Technical report: the study of H5N1 based on SIR Model / Nurul Najihah Zubir, Nur Adibah Azmi and Nor Deena Mohd Isa - Zubir, Nurul Najihah; Azmi, Nur Adibah; Mohd Isa, Nor Deena (2017)
There are two scenarios created on the human part of the H5N1 model.They are prepandemic scenario model and pandemic scenario model. Prepandemic scenario model is the model of the current situation where humans infected. with avian flu via bird versus human infection. Meanwhile, the pandemic scenario model is the model for a hypothetical scenario in which a pandemic strain arises and humans have been infected via human to human transmission. In this research, we are only focusing on the prepandemic scenario model. It is because we want to clearly understand how humans can be infected via bird transmission. In this case, we consider the domestic birds only. As a whole, this research is restricted to highly pathogenic H5N1 avian influenza and we include the domestic bird population only. The aim of this research is to derive the models of both epidemic which are among domestic birds by SI model(Susceptible -infected) and among humans by SIR model( Susceptible-Infected-Recovered). These modified models are derived from each variables to determine their relationship with each other. Second, we fit the data into that model. Then we plot a graph by using MAPLE software to display the results. Furthermore, we discuss the graph as in section result and discussion.